Export diversification and economic growth in Bangladesh - Azam, Musharrat; Azam, Samiha (Journal of Empirical Studies, 2023)
Although the growth in exports of Bangladesh over the past few decades has been exemplary, it is enormously concentrated on just one industry which is the Ready Made Garment (RMG) sector. This over dependence on just one sector for export earnings places Bangladesh in a vulnerable position. This study examined the relationship between export diversification and growth rate of the Gross Domestic Product (GDP) of Bangladesh using annual data from 1995 to 2020. The study utilized the Autoregressive Distributed Lag (ARDL) bounds test to cointegration approach to estimate the long run relationship and the error correction model to determine the existence of a short run relationship. The results from the study indicate that there exists a significant long run cointegrating relationship between overall export diversification and economic growth in Bangladesh. In the long term, if horizontal export diversification increases by 1%, the GDP growth rate shall rise by around 1.7%. Conversely, the short run relationship between export diversification and economic growth is proven to be insignificant. The results of this study implore that Bangladesh should implement strategies and policies that will diversify its exports and shift away from the dominance of just one exporting sector.